2013
DOI: 10.1590/s0034-8910.2013047004011
|View full text |Cite
|
Sign up to set email alerts
|

Aerossois de queimadas e doencas respiratorias em criancas, Manaus, Brasil

Abstract: OBJECTIVE:To investigate the effects of fi ne particulate matter emitted through biomass burning on hospitalizations for respiratory diseases in children living in Manaus, Northern Brazil. METHODS:Descriptive study with ecologic time series design carried out in Manaus from 2002 to 2009. Hospital admission data were obtained from the Unifi ed Health System database. PM 2.5 levels were estimated using aerosol remote sensing through the measurement of aerosol optical depth at a wavelength of 550 nm. Statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 16 publications
2
21
0
15
Order By: Relevance
“…The findings of this study agree with those of other national articles7 , 10 , 11 and the results of Hertz-Picciotto et al,25 who pointed out the role of this pollutant in hospitalizations for lower respiratory tract infections in preschool children in the Czech Republic. Karr et al,13 using conditional logistic regression, showed that exposure to PM 2.5 was associated with increased risk of hospitalization for childhood bronchiolitis (OR=1.09; 95%CI: 1.04–1.14).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of this study agree with those of other national articles7 , 10 , 11 and the results of Hertz-Picciotto et al,25 who pointed out the role of this pollutant in hospitalizations for lower respiratory tract infections in preschool children in the Czech Republic. Karr et al,13 using conditional logistic regression, showed that exposure to PM 2.5 was associated with increased risk of hospitalization for childhood bronchiolitis (OR=1.09; 95%CI: 1.04–1.14).…”
Section: Discussionsupporting
confidence: 93%
“…Os achados deste estudo concordam com os de outros artigos nacionais7 , 10 , 11 e com os resultados de Hertz-Picciotto et al .,25 que apontaram o papel desse poluente nas internações por doenças do trato respiratório inferior em pré-escolares da República Checa. Karr et al .,13 com o uso da regressão logística condicional, mostraram que exposições ao PM 2.5 estiveram associadas ao aumento do risco para hospitalização por bronquiolite infantil (OR=1,09; IC95%: 1,04-1,14).…”
Section: Discussionunclassified
“…Note that PM 2.5 concentrations ranged from 13 µg/ m 3 in the rainy season to 21 µg/m 3 in the dry season. 25 In our study, the concentrations estimated by the CATT-BRAMS were within the range of estimated values for Cuiabá, MT, and Piracicaba, SP. The increase in the concentration of PM 2.5 in São José do Rio Preto would imply an increase between 23 and 26% in the risk of hospitalization, and these increases are close to those found in Cuiaba in the dry season.…”
Section: Discussionsupporting
confidence: 83%
“…These factors contribute to the advection of particles, because there is less deposition in August, and majority cases of biomass burning occurred during August and September (Filho et al, 2013). In August 2010 (Figure 4(c)), we observed many pixels with AOD values >2.0, with some pixels having values >4.0.…”
Section: Aerosol Transport During Wintermentioning
confidence: 85%